1995
DOI: 10.1523/jneurosci.15-06-04238.1995
|View full text |Cite
|
Sign up to set email alerts
|

Kainic acid-induced neuronal death is associated with DNA damage and a unique immediate-early gene response in c-fos-lacZ transgenic rats

Abstract: Previously, we established that persistent upregulation of c-fos expression preceded kainic acid (KA)-induced neuronal death in mice. To discriminate between events that are products of the seizures elicited by KA and those that are specifically associated with its neurotoxic actions, we have examined the expression of cellular immediate-early genes (cIEGs) following KA or pentylenetetrazol (PTZ) treatment in c-fos-lacZ transgenic rats. While both chemoconvulsants elicit seizures, only KA causes selective neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 41 publications
6
86
0
3
Order By: Relevance
“…Recent studies demonstrated the protracted expression of AP-1-like DNA-binding activity in the rat brain after chronic cocaine administration, electroconvulsive shock, and drug-induced seizure activity (Hope et al, 1992(Hope et al, , 1994aKaminska et al, 1994;Pennypacker et al, 1994;Kasof et al, 1995). Figure 1A shows that this phenomenon also occurs in the mouse.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Recent studies demonstrated the protracted expression of AP-1-like DNA-binding activity in the rat brain after chronic cocaine administration, electroconvulsive shock, and drug-induced seizure activity (Hope et al, 1992(Hope et al, , 1994aKaminska et al, 1994;Pennypacker et al, 1994;Kasof et al, 1995). Figure 1A shows that this phenomenon also occurs in the mouse.…”
Section: Resultsmentioning
confidence: 88%
“…Although this is theoretically possible, multiple probes from different regions of the fosB mRNA fail to detect additional transcripts by in situ hybridization and Northern blotting (Fig. 5) (Z erial et al, 1989;Nakabeppu and Nathans, 1991;Kaminska et al, 1994;Chen et al, 1995;Kasof et al, 1995). Therefore, the most likely explanation is that the 37 kDa ⌬-FosBlike protein has a very long half-life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 However, c-fos expression is also seen in neurons committed to apoptosis. 20 The c-jun gene has been linked to neuronal apoptosis 21 and neuronal rescue. 6 Ischemia also upregulates Cox-2 expression; we observed a peak at 1 hour and continued strong expression at 4 hours.…”
Section: Discussionmentioning
confidence: 99%